Toksisitas Subkronis Ekstrak Biji Salak (Salacca Zalacca) Terhadap Fungsi Hati Mencit Putih - Octasari, Paulina Maya; Rukminingsih, Fef; Vita, Cristin Yulia (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2023)
Salak seeds (Salacca zalacca) contain several secondary metabolites like as 0.059% flavonoids, 0.082% tannins and 0.063% alkaloids. Salak is a potential plant as a medicinal ingredient, so it is necessary to conduct a drug safety study. Subchronic toxicity test needs to be done in traditional drug therapy because it is given continuously. This study objective was to examine the subchronic toxicity of salak seed extract on liver function in male Swiss strain mice. This type of research is an experimental study with a completely randomized design with a one-way pattern with one treatment factor. There are four treatment groups with a total of 7 mice replications. Variations in the dose of salak seed extract administration were 91 mg/20 gBW of mice, 114 mg/20 gBW of mice, and 137 mg/20 gBW of mice. The toxicity test were SGPT and SGOT values on days 0 and 14. The data tested with one-way ANOVA followed by a t-test. The Salak Seed Extract (EBS) is a viscous extract with a dark brown colour, a distinctive smell of salak, and a chelate taste. The amount of the extraction result was 12.26%. Positive EBS contains flavonoids with a reddish-orange colour. The treatment of Salak Seed Extract ( 91 mg/20 g BW and 137 mg/20 g BW) was not increased significantly the SGPT and SGOT levels for 14 days (p-value 0.896 and 0.072). Although the second dose (114 mg/20 g BW) was increased the SGPT and SGOT levels (p-value 0.002), this enhancement was less than twice